Peru : Report on the Statistics Technical Assistance and Training Evaluation Mission (December 12. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses the evaluation of technical assistance (TA) and training provided by the Statistical Department (STA) of the IMF to Peru during 1993-2011. The results showed that TA was reasonably effective, especially in the areas of government finance statistics, and responded well to the demands expressed by the Peruvian authorities. Many constraints to capacity were overcome through TA and training. The evaluation also found that the quality of TA reports, backstopping, and report management in STA were generally adequate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet